Facing the climate change conundrum at the South Pole: actors’ perspectives on the implications of global warming for Chilean Antarctic governance - Gladkova, Ekaterina; Blanco-Wells, Gustavo; Nahuelhual, Laura (Polar Research, 2018)
Antarctica is recognized as being geopolitically and scientifically important, and as one of the regions with the greatest potential to affect and be affected by global climate change. Still, little is known in practice about how climate change will be handled within the main governance framework of the continent: the Antarctic Treaty System (ATS). Using qualitative interviews, participant observations and policy document analysis, this paper explores the perspectives of Chilean scientific, political and non-governmental actors regarding the implications of climate change for the current Antarctic governance framework. Results corroborate a misalignment of the climate change agenda and the ATS, stemming from the divergent views displayed by a wide network of actors. From the interviews, two predominant visions emerge: (i) climate change as an opportunity, where actors recognize the role of Antarctica in regulating global climate and stress greater opportunities to conduct Antarctic-based climate change research, the need for strategic international collaboration, and the reinforcement of Chile’s position in Antarctica through science; (ii) climate change as a burden where actors acknowledge climate change as a global problem, largely external to Antarctica, express disbelief regarding the effectiveness of local actions to tackle climate change and do not associate with climate change governance. The study concludes that climate change may become a dividing, rather than a unifying, field of action in Chilean Antarctic governance, reinforcing previously existing geopolitical tendencies.
Keywords: Antarktis; Antarktistraktaten; geopolitikk; klimaendringer; vitenskap